2015
DOI: 10.1021/acsphotonics.5b00486
|View full text |Cite
|
Sign up to set email alerts
|

Linearly Polarized Excitons in Single- and Few-Layer ReS2 Crystals

Abstract: Rhenium disulfide (ReS2), a layered group VII transition metal dichalcogenide, has been studied by optical spectroscopy. We demonstrate that the reduced crystal symmetry, as compared to the molybdenum and tungsten dichalcogenides, leads to anisotropic optical properties that persist from the bulk down to the monolayer limit. We find that the direct optical gap blueshifts from 1.47 eV in the bulk to 1.61 eV in the monolayer limit. In the ultrathin limit, we observe polarization-dependent absorption and polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
314
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(356 citation statements)
references
References 39 publications
38
314
3
1
Order By: Relevance
“…This possibility requires further exploration, both experimentally and theoretically, but it may point to the presence of rather strongly bound excitons even in bulk ReS 2 . This would seem broadly consistent with the observed pronounced excitonic features in optical spectra [5,42].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This possibility requires further exploration, both experimentally and theoretically, but it may point to the presence of rather strongly bound excitons even in bulk ReS 2 . This would seem broadly consistent with the observed pronounced excitonic features in optical spectra [5,42].…”
Section: Resultssupporting
confidence: 89%
“…The nature of the optical band gap in ReS 2 has proved controversial, with an indirect band gap suggested by recent optical measurements [42]. To investigate this in more detail, we have performed This is located only 28 meV higher in energy than the calculated valence-band eigenstates at the Z point.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast ReS2 has reduced crystal symmetry which gives rise to anisotropic inplane optical properties. [21,51,[70][71][72] Research related to the electron-electron and hole-hole interactions in the excited state concluded that the anisotropic optical absorption on ReS2 was due to strongly bound excitons. The triclinic crystal structure of ReS2 leads to polarization dependent optical absorption.…”
Section: Excitonic and Absorption Propertiesmentioning
confidence: 99%
“…However, there exist a small number of materials with strong in-plane structural anisotropy. Some examples of these materials are black phosphorus, 7,13,14 group-V TMDCs (ReS 2 and ReSe 2 ), 11,12 and transition metal trichalcogenides (MX 3 ). [15][16][17][18][19] These materials differ from isotropic layered materials in that each individual layer consists of a superlattice of 1D chains extending along one particular lattice direction.…”
Section: Introductionmentioning
confidence: 99%
“…7,13,14,21 More recently, the Raman/PL spectrum, and polarized photodetector applications have been investigated in ReS 2 and black phosphorus. 11,12,[22][23][24]42 Despite these pioneering studies, our understanding of pseudo-1D materials, particularly TMTCs with the chemical formula MX 3 (M = Zr, Ti, Hf and X = S, Se, and Te), is still in its infancy. TMTCs are a new class of layered materials with strong in-plane anisotropy.…”
Section: Introductionmentioning
confidence: 99%